Implementation of the Wadiah Contract in the Practice of the Eid Savings Scheme from the Fathul Qorib Perspective - Afida Mariani Kamila; Lely Ana Ferawati Ekaningsih (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze the implementation and sharia compliance of the wadiah yad dhamanah contract in the tabungan hari raya (holiday savings) product at uspps blokagung-banyuwangi through a qualitative case study. Using the Kitab Fathul Qorib as the primary normative perspective, data was collected through interviews, observation, and document studies, and then analyzed using the Miles and Huberman interactive model. The findings indicate uncertainty, despite the formal fulfillment of the contract's pillars through the application of wadiah yad al-dhamanah. An in-depth analysis reveals three substantive deviations. First, the customers' low understanding of the nature of the trust (deposit) contract creates gharar (uncertainty) and erodes the principle of ridha (mutual consent) emphasized in Fathul Qorib. Second, the practice of a fixed, promoted